Re-evaluating electronic government development index to monitor the transformation toward achieving sustainable development goals - Osman, Ibrahim H.; Zablith, Fouad (Journal of business research, 2021)
•Sub-indices of EGDI have different importance using data-driven Shannon Entropy.•Data Envelopment Analysis efficiency and effectiveness indices are introduced.•Efficiency and effectiveness values show a declining effort toward achieving SDGs.•New proposed analytics methods question the current UN ranking of countries.•How to improve ranking and set realistic targets from best peers are provided. While the connection between the electronic government development index (EGDI) and sustainable development goals (SDGs) is well established, global efforts to provide appropriate means for achieving SDGs remain insufficient. This study addresses this issue by introducing a hybrid framework using Shannon entropy to derive data-driven weights for aggregation, technique for order preference by similarity to ideal solution for relative ranking, and data envelopment analysis for generating performance efficiency and effectiveness indices, benchmarks for setting targets, and analytical insights for smarter decisions and managerial actions. The hybrid methods are validated on the 2014, 2016 and 2018 EGDI datasets that cover 193 countries. Our findings illustrate a significant change in the weights of performance indices, leading to a change in the ranks of over 90% of the countries, and a decrease in the SDG performance trend due to less efficient utilization of resources, despite an increase in the effectiveness of outcomes.